A Strongly Fluorescent Molecular Material Responsive to Physical/Chemical Stimuli and their Coupled Impact. Issue 24 (16th October 2019) - Sudhakar, Pagidi; Radhakrishnan, T. P.
Abstract: Molecular materials with weak but extended and pliable supramolecular interactions are versatile candidates for eliciting stimuli‐sensitive optical responses. A novel diaminodicyanoquinodimethane (DADQ) molecule, 7, 7‐bis(2‐(2‐pyridyl)ethylamino)‐8, 8‐dicyanoquinodimethane (BPEDQ), has been synthesized and structurally characterized; it exhibits enhanced fluorescence emission in the aggregated and solid states, characteristic of DADQs. The pyridine moieties in the molecule, in addition to the amino and cyano groups of the strongly dipolar fluorophore moiety, induce extensive H‐bonding interactions which can impart structural integrity to the solid material; this enables reversible crystalline‐amorphous transformations triggered by mechanical grinding and solvent fuming. The concomitant fluorescence color and intensity switching are prominent and reversible. Protonation‐deprotonation events induced by acidic and basic vapors also produce stark fluorescence response variations; the chemical stimuli also lead to amorphization of the solid. The full cycle of chemical and physical stimuli, and the consequence of their individual and coupled impact on the fluorescence emission, are illustrated using a BPEDQ‐doped polymer thin film. Abstract : A diaminodicyanoquinodimethane‐based compound is shown to exhibit strong fluorescence emission which can be switched as well as quenched and recovered reversibly by mechanical and chemical stimuli.